PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI - B51110047, Sherly Silvianty (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2014)
This research aims to know the influence of Intellectual Capital on the company's profitability of transportation sub sectors listed on the stock exchange. Proftability ratio used is return on assets ratio, return on equity ratio, net profit margin ratio, and return on investment ratio. Collecting data using purposive sampling method of basic transportation sub sectors listed on the stock exchange in 2010 until 2012. A total of 10 companies qualified as research samples. Methods of data analysis using simple regression analysis. The results of this research indicate that the independent variables, namely Intellectual Capital, negative and significant effect on the ratio of ROA, ROE, NPM and ROI of the company. This research same with Sigit Hermawan dan Maharis Budi Wahyuaji (2013) research which also have result that Intellectual Capital has negative and significant effect on the ratio of ROA (Return On Asset)Â  and ROE (Return On Equity) and no significant effect between Intellectual Capital with NPM (Net Profit Margin). Keywords: Intellectual Capital, Profitability, ROA, ROE, NPM, ROI, VAIC